HUBUNGAN STATUS EKONOMI DAN RIWAYAT ASI EKSLUSIF DENGAN RESIKO STUNTING PADA BALITA USIA 24-59 BULAN DI WILAYAH KERJA PUSKESMAS PERAWATAN NAPAL PUTIH KECAMATAN NAPAL PUTIH 2023 - Melia Eka; Muhammad Hatta (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2023)
Background: Stunting is a problem of long-term (chronic) nutritional problems which has an impact on growth disorders, especially in tall people and is very vulnerable to various infectious diseases. Purpose: To find out whether there is a relationship between economic status and a history of exclusive breastfeeding with the risk of stunting in toddlers aged 24-59 months in the Working Area of ​​the Napal Putih Health Center, Napal Putih District. Research Methods: The research design used a quantitative approach with a cross-sectional research type. The population in the study was all toddlers in the Working Area of ​​the White Napal Treatment Health Center, totaling 942. The sample of this study used the quota sampling method, where the number of samples in this study amounted to 60. toddler. Data analysis through univariate analysis based on the distribution of frequency distribution and bivariate analysis. Results: Stunted toddlers in the Working Area of ​​the White Napal Care Health Center are known to have a family economic status factor for the incidence of stunting shown by a p-value of 0.004, there is a relationship between a history of exclusive breastfeeding and the risk of stunting, a p-value of 0.006 is obtained. Conclusion: There is a relationship between family economic status and history of exclusive breastfeeding with the risk of stunting in toddlers 24-59 months in the Working Area of ​​the Napal Putih Health Center, Napal Putih District 2023 Keywords: Family Economic Status, History of Exclusive Breastfeeding, Stunting